Community Empowerment through Health Promotion Regarding Prevention of the Spread of COVID-19 in East Java - Linda Presti Fibriana; Nuris Kushayati; Heti Aprilin; Anik Supriani; Nasrul Hadi Purwanto (Journal for Quality in Public Health, 2021)
ABSTRACT Organization (WHO) as a pandemic, namely a disease that is transmitted globally (global outbreak). The Covid-19 pandemic as a non-natural disaster is becoming increasingly "dangerous" if it is not addressed immediately because experts have yet to find the most effective drug and vaccine. This study aims to determine community empowerment through health promotion on preventing the spread of Covid-19 in East Java. The research method used in this research is a qualitative design. Data collection was carried out through in-depth interviews with due observance of health protocols and by using FGD (focus group discussion) on 158 participants through zoom meetings. Data were analyzed using thematic analysis. The results show that to achieve a healthy state, a person or group must be able to identify and be able to meet needs and change or control the environment. Prevent the spread of Covid-19 by washing your hands frequently with soap/hand sanitizer and applying cough etiquette. Improve health with community movements such as consumption of balanced nutrition, diligent exercise, adequate rest and frequent washing of hands with soap. It is concluded that prevention and control of the spread of Covid-19 through health promotion by empowering the community to achieve a healthy state, a person or group must be able to identify and realize aspirations, be able to meet needs and change or control the environment. Keywords: Community empowerment, Spread Prevention, Health Promotion, Covid-19